A Phytopharmacological overview on Tecomella undulata G. Don - Jagbir Chal, Vinod Kumar, Sunil Kaushik (Journal of Applied Pharmaceutical Science)
Tecomella undulata G. Don. is a popular medicinal plant has long been used in ayurvedic system of medicine. The plant has been found to exhibit diverse pharmacological activities. The present paper gives an account of updated information on its photochemical and pharmacological properties. The review of literature reveals that wide range of phytochemical constituents have been isolated from plant and it possesses important pharmacological activities like antibacterial, anticancer and its utility in treatment of certain ailments like syphilis, swelling, leucorrhoea and leucoderma, enlargement of spleen have also been reported. The reports are encouraging hence the herb must be extensively used for its therapeutic benefits. Also the study based on clinical trials should be carried out to support the usage of drug traditionally for treatment of various ailments.